Labor markets in Latin America : combining social protection with market flexibility - Edwards, Sebastian, 1953-; Lustig, Nora.; Brookings Institution (Washington, D.C. : Brookings Institution Press, 1997)
Many of the rules that govern labor markets in Latin America (and elsewhere) raise labor costs, create barriers to entry, and introduce rigidities in the employment structure. These include the exceedingly restrictive regulations on hiring and firing practices, as well as burdensome social insurance schemes. Such labor market regulations contribute to an over-expansion of precarious forms of employment and to rural poverty, and hinder countries from responding rapidly to new challenges from increased foreign competition. At the same time, other norms can reduce costs and raise productivity; th.
7. Brazil: Regulation and Flexibility in the Labor Market -- 8. Chile: The Evolution and Reform of the Labor Market -- 9. Colombia: The Evolution and Reform of the Labor Market -- 10. Mexico: The Evolution and Reform of the Labor Market -- Contributors -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W
Proceedings of a conference which was held in Buenos Aires, Argentina, Universidad di Tella, July 6-7, 1995.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Labor market -- Latin America; Manpower policy -- Latin America; Labor laws and legislation -- Latin America; Marché du travail -- Amérique latine; Emploi -- Politique gouvernementale -- Amérique latine; BUSINESS & ECONOMICS -- Labor; Labor laws and legislation; Labor market; Manpower policy; Latin America; BUSINESS & ECONOMICS / Labor / General